Engineered Bacterial Outer Membrane Vesicles as Multifunctional Delivery Platforms - Li, Ruizhen; Liu, Qiong (Frontiers in Materials, 2020)
Outer membrane vesicles (OMVs) are valued for their unique, convenient, and amendable functions. They are flexible, controllable nanoparticles, which can be modified in different ways, for use in a wide array of applications like adjuvants, vaccines, drug presentation, and fluorescence tracking. Attempts have been made to alter the nanoparticles in liposomes and bacterial ghosts using traditional methods. However, it has not been highly successful owing to certain unavoidable disadvantages. OMVs have unique advantages and are considered novel platforms for heterologous protein presentation. Although previous reviews have described this to some extent, owing to the rapid development in this field, there is a need for the regular update of the reviews. This review focuses on few novel applications of engineered OMVs, and redefines the significance of OMVs as novel multifunctional delivery platforms. Additionally, this review also supplements and provides an update on the OMV transformation methods.